(untitled) (Philological Studies, 2019)
The reader is offered an overview of the development of Roman Ingarden’s phenomenology of literature. The author of this paper proceeds from the position that this theoretical approach has not yet exhausted itself and actualizes it as a means of intercultural communication. Polish philosopher R. Ingarden is known primarily for his interpretation of a work of art as a special form of being. The geopolitical position of Poland contributed to the reception of European philosophy, the formation of national thinkers known abroad. Ingarden solves questions of ontology, consciousness, epistemology, metaphysics, ethics and axiology on the example of the phenomenology of literature. The thinker seeks to bring the teachings on the acts of consciousness to a more realistic position, and therefore refers to a literary work as an example of the layering of the being. R. Ingarden introduces such characteristics of sociocultural objects as intentionality, points of uncertainty and concretization, which makes it possible to consider his phenomenological methodology as a versatile tool for analyzing text in culture.